ANALISIS UPAYA GURU DALAM MENGATASI KESULITAN BELAJAR SISWA SMK PADA MATA PELAJARAN AKUNTANSI - Rena Wijayanti; Erni Harlina Isdiati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to determine the forms of learning difficulties experienced by students as well as teachers` efforts in overcoming learning difficulties in accounting subjects in class X-AKL at SMK PGRI 1 Semarang. This study uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, documentation, and recordings. The research subjects consisted of 20 students and accounting teachers selected using purposive sampling. The results of the study show that students experience obstacles in understanding basic accounting concepts, especially in the material of general journals and adjusting journals. The factors causing learning difficulties are influenced by internal factors such as low students' interest and learning motivation, as well as external factors such as less conducive classroom conditions and the teaching methods applied by teachers. Teachers' efforts in overcoming learning difficulties are carried out through gradual explanation of material, providing practice questions, implementing remedial programs, and group learning activities. Based on the research results, it can be seen that teachers` efforts in overcoming students` learning difficulties have been running quite well, although there are still several obstacles in the implementation process. ABSTRAK Penelitian ini bertujuan untuk mengetahui bentuk kesulitan belajar yang dialami siswa serta upaya guru dalam mengatasi kesulitan belajar pada mata pelajaran akuntansi di kelas X-AKL SMK PGRI 1 Semarang. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa wawancara, observasi, dokumentasi, dan rekaman. Subjek penelitian terdiri dari 20 siswa dan guru akuntansi yang dipilih menggunakan purposive sampling. Hasil penelitian menunjukkan bahwa siswa mengalami hambatan dalam memahami konsep dasar akuntansi, terutama pada materi jurnal umum dan jurnal penyesuaian. Faktor penyebab kesulitan belajar dipengaruhi oleh faktor internal seperti rendahnya minat dan motivasi belajar siswa, serta faktor eksternal seperti kondisi kelas yang kurang kondusif dan metode pembelajaran yang diterapkan guru. Upaya guru dalam mengatasi kesulitan belajar dilakukan melalui penjelasan materi secara bertahap, pemberian latihan soal, pelaksanaan program remidial, dan kegiatan belajar kelompok. Berdasarkan hasil penelitian, dapat diketahui bahwa upaya guru dalam mengatasi kesulitan belajar siswa sudah berjalan cukup baik, meskipun masih terdapat beberapa hambatan dalam proses pelaksanaannya.